Strategi Pembelajaran di Era Postmodern: Peningkatan Hasil Belajar Melalui Pendekatan Active Learning pada Generasi Digital Native - Boini, Boini; Sahrul, Sahrul; Wahab, Wahab; Kurniawan, Syamsul (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2024)
Motivation, from time to time, including the postmodern era, becomes one of the success factors in learning. However, today, student motivation is low, which has a major impact on students learning outcomes. Accordingly, teachers need to use various strategies to motivate students in learning in order to get maximum learning results. This study aims to describe the right strategy to overcome the boredom of students of digital native generation so that literacy index and learning outcomes increase, especially in Islamic Education for students at the kindergarten level. This study used a qualitative method with the type of phenomenology, in which researchers tried to understand understand the behavior, motivation, perception, and action of the research subjects. The data collection techniques used were interviews, observation and documentation. The results of this study show that active learning strategies are very relevant to improve student learning outcomes and can encourage student learning motivation. The learning process is carried out through games, quiz, verse connection games, index card matches, discussions, and questions-answers.